Design metaphor to improve interface usability for paddy farmers in Malaysia using user-centered approach - Jamalai @ Jamali, Siti Nurliana; Admodisastro, Novia Indriaty; Kamaruddin, Azrina; Hassan, Sa'adah; Din, Jamilah (University Community Transformation Centre, Universiti Putra Malaysia, 2017)
Metaphor is a representation of object and situation that have meaning and comparable to real thing to convey the message to people. The purpose of using metaphor is to facilitate in making communication more direct and effective for particular user communities. This study reveals design metaphor issues for paddy farmer population in agriculture domain in Malaysia. The work is motivated by the ICT-Based Agriculture Flagship Blueprint of the Malaysia Government, an initiative to equip agriculture stakeholders in Malaysia including farmers with ICT knowledge on multiple platforms e.g. kiosk, personal computer or mobile devices. The metaphors design is deemed to have a huge potential to improve usability for paddy farmers in Malaysia. The work is conducts using user-centered design approach. This approach allows higher degree of paddy farmers’ involvement during the development process. Also, to be able to obtains deeper understanding of the farmers’ background, tasks and environment. The study has derived a guidelines of metaphor design as well as development of design metaphors based on the guidelines. A prototype of mobile paddy application is developed to demonstrate the practicality of the design metaphors. The design metaphors then are evaluated by conducting usability testing to the farmers. The result is gathered and being assessed by using descriptive statistics.